2001
DOI: 10.1063/1.1412601
|View full text |Cite
|
Sign up to set email alerts
|

The unimolecular dissociation of HCO. V. Mixings between resonance states

Abstract: Articles you may be interested inVibrationally quantum-state-specific dynamics of the reactions of CN radicals with organic molecules in solution

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 25 publications
1
14
0
Order By: Relevance
“…All four profiles obtained were simultaneously fitted by a numerical solution of a system of differential equations corresponding to the reaction mechanism. The reaction mechanism used in the fits includes reactions (1-3) and additional reactions (7)(8)(9)(10)(11):…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…All four profiles obtained were simultaneously fitted by a numerical solution of a system of differential equations corresponding to the reaction mechanism. The reaction mechanism used in the fits includes reactions (1-3) and additional reactions (7)(8)(9)(10)(11):…”
Section: Resultsmentioning
confidence: 99%
“…The only one possibility for an interfering process to lead to a decrease of the apparent rate constant is in reactions leading to the reproduction of formyl radicals (such as reactions (8b) and (9b)). Very little is known about these channels of reactions (8) and (9). To check out such a possibility, the experiments with the photolysis of acetaldehyde at 193 nm (where it has a ''hot'' absorption) were designed to evaluate the role of the secondary reaction of methyl radicals and hydrogen atoms with the precursor molecule.…”
Section: Unimolecular Dissociation Of Formyl Radicals-resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Anharmonic resonances induced by variations of J and/or K are common effects in small molecules. They have been also observed for HCO and HNO [36,37]. For these two molecules, however, the resonance widths are considerably larger Ϫ and therefore less sensitive with respect to slight changes of the level structure Ϫ than for state (6,0,0) of HOCl and the mean spacing between the levels is comparatively large.…”
Section: Discussionmentioning
confidence: 74%
“…The latter are due to interactions between different states. For the HCO radical, Schinke and coworkers [126] found that rotational motion can influence the resonance widths in so far as a fine tuning with respect to energy is achieved via distinct rotational constants in different vibrational states. A similar scheme applies here, where, however, the fine tuning results from differences in the intermolecular wavenumber for the different progressions.…”
Section: Four-dimensional Calculationsmentioning
confidence: 99%